RtxA like protein contributes to infection of Francisella novicida in silkworm and human macrophage THP-1. (October 2018) - Saha, Shib Shankar; Uda, Akihiko; Watanabe, Kenta; Shimizu, Takashi; Watarai, Masahisa
Abstract: Tularemia is a zoonosis caused by CDC-declared Tier 1 threat agent Francisella tularensis . F. tularensis subsp. novicida ( F. novicida ) is virulent in mice but non-pathogenic in immunocompetent humans and serves as a potential surrogate organism. In a recent study, we established a silkworm ( Bombyx mori ) model of infection for F. novicida . Francisella secretes its virulence factors through various mechanisms that modify the intracellular environment to ensure its replication and survival. To identify new pathogenic factors, we focused on the type I secretory system (T1SS) of Francisella . In silico analysis revealed a RtxA (Repeats-in-toxin) like protein in the Francisella genome. The characteristics of RtxA like protein were investigated using mutant analysis. Firstly, the role of rtxA in silkworms was investigated by infecting them with F. novicida strains into the hemocoel. The rtxA mutant failed to kill the silkworms, whereas F. novicida wild-type (WT) strain killed silkworms within 3–7 days post infection. The arrested growth of the mutant strain in silkworms was observed using a whole-body CFU count assay. We also investigated the growth characteristics of the rtxA mutant in hemocytes, one of the primary multiplication sites of Francisella within silkworms. Interrupted growth of the rtxA mutant with significantly reduced cytotoxicity was observed in hemocytes via confocal microscopy. Next, we analyzed the effect of rtxA in human monocyte cell line THP-1. The mutant strain showed significantly decreased growth and reduced cytotoxicity compared with its parental strain in THP-1 cells. This study newly identified RtxA like protein of F. novicida as an important lethal pathogenic factor in silkworm and mammalian cells. Highlights: There is a RtxA like protein in Francisella novicida. The deletion mutant of RtxA like protein failed to kill silkworm. RtxA like protein contributes to intracellular growth in THP-1 cells.